Letras, ladeiras e o cuidar de si: autoetnografia de um artista periférico - Ceriaco, Michel da Silva da (Universidade Federal de São Carlos, 2023)
This dissertation presents the biography of a black writer and cultural producer from the outskirts of São Paulo, starting in the 1990s. Through a qualitative autoethnographic research, it starts from his encounter with Hip Hop and Rap, in dialogue with other works by artists and collectivities, to describe and analyze, in the recent context, the expansion of the focus and actions of cultural movements from the periphery around themes such as health, self-care, take care of yourself, and good living. It takes as a starting point the studies of Daniela Versiani and Fabiene Gama on autoethnography; analyzes of cultural movements in the periphery, by Érica Peçanha and Renato Almeida; Rap and Hip Hop, by Ricardo Plácido, Marília Sposito and Guilherme Botelho; the theories of Grada Kilomba and Sueli Carneiro on the silencing, disqualification and annulment of the discourse of black people in hegemonic spaces, as well as reflections on the potential spaces of life and good living, according to Kota Mulangi and Alberto Acosta. Considering the importance of the educational processes that occur beyond the school walls, it shows how artistic collectivities promote new theoretical and practical perspectives to reinvent the protagonism and the way of being and being in the peripheries, as well as the re-elaboration of the subjects' thinking and practice /as and collectives from the outskirts on topics such as health, self-care, take care of yourself and good living.
Letters, slopes and self-care: autoethnography of a peripheral artist
Keywords: Autoetnografia; Periferias; Arte; Produção cultural; violência; Relações étnico-raciais; Saúde; Cuidado de si; autoethnography; peripheries; art; cultural production; violence; ethnic-racial relations; health; take care of yourself; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO